Factors influencing users adoption of electronic payment in Jinzhong City, China - Haodong, Ren (2019)
Electronic payment is a payment method that has been adopted in China in recent years. The rapid development of electronic commerce in China has promoted the development of electronic payment. In the electronic transaction, users can use mobile phones to quickly complete the payment process through the network. Electronic payment is very popular among Chinese people because of its simple operation and high efficiency. This paper studies the factors affecting the continued use of electronic payment by Chinese users. In this study, TAM model is cited and a research framework is established. Five hypotheses are put forward for the factors affecting users' continuous use of electronic payment. In addition, this study uses quantitative research methods to investigate and analyze the use of electronic payment. Then SPSS 25 is used for data analysis to conduct reliability, correlation analysis and test hypothesis. The results show that security, convenience, perceived usefulness, perceived ease of use and attitude are all related to users' adoption of electronic payment. These five factors are the factors that affect users' continued use of electronic payment. Therefore, these research results provide practical and theoretical guidance for operators of electronic payment platforms and subsequent related research.